Optimizing equine standing sedation: continuous infusion of detomidine and butorphanol enhances stability but prolongs ataxia - Arantes, Julia de Assis; Rabelo, Isabela Peixoto; Bermudes, Lucas; Lacerenza, Milena Domingues; Mendes, Rubens Peres; Corrêa, Rodrigo Romero; Yamada, Diego Iwao; Valadão, Carlos Augusto de Araújo; Dória, Renata Gebara Sampaio (Frontiers in Veterinary Science, 2025)
ObjectiveThis study aimed to compare the sedation quality and cardiorespiratory and behavioral effects of detomidine administered intravenously, either in intermittent boluses or as a continuous rate infusion, with butorphanol in horses pre-medicated with acepromazine for odontoplasty procedures.MethodsA prospective clinical study was conducted with fifteen adult horses randomly assigned to two groups: Bolus group (BG, n = 7) and Infusion group (IG, n = 8). Both groups received acepromazine premedication, followed by detomidine administration (bolus or infusion). Butorphanol was administered either as a bolus or continuous infusion during oral cavity evaluation (after detomidine). When sedation was inadequate, an additional bolus of detomidine combined with butorphanol was given. Physiological, sedative, and behavioral parameters were evaluated at multiple time points throughout the procedure. Data were analyzed using statistical models to assess differences between groups and across time points.ResultsContinuous infusion of detomidine resulted in superior sedation quality, greater stability, and a reduced need for rescue sedation (p < 0.001) compared to bolus administration. Horses in the BG total detomidine consumption was significantly influenced by procedure duration and the number of readministrations (p = 0.004). Despite improved sedation quality in IG, ataxia persisted longer post-procedure. Cardiovascular parameters showed expected α2-agonist effects, with transient reductions in heart rate and stable arterial pressure.Conclusions and clinical relevanceContinuous infusion of detomidine with butorphanol provided more stable sedation, reducing the need for frequent redosing, but also led to prolonged ataxia. Future studies should explore alternative drug combinations to optimize sedation quality while minimizing ataxia and cardiorespiratory effects.